2016
DOI: 10.1177/0284185116658681
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels in low- and middle-income countries: early “ALARAm” bells?

Abstract: Background: In 1996 the International Commission on Radiological Protection (ICRP) introduced diagnostic reference levels (DRLs) as a quality assurance tool for radiation dose optimization. While many countries have published DRLs, available data are largely from high-income countries. There is arguably a greater need for DRLs in low-and middleincome-countries (LMICs), where imaging equipment may be older and trained imaging technicians are scarce. To date, there has been no critical analysis of the published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Die Vorteile und Erfolge dieser Bildgebung sind anerkannt, es bedarf aber auch heute immer einer rechtfertigenden Indikation, auch zur Röntgendiagnostik. Der kindliche Organismus ist im Vergleich zum Erwachsenen strahlensensibler und damit anfälliger, durch ionisierende Strahlen Malignome zu entwickeln, auch weil die jungen Patienten eine längere Lebenserwartung und damit Zeitspanne haben [ 7 , 30 , 41 , 46 ].…”
Section: Diskussionunclassified
“…Die Vorteile und Erfolge dieser Bildgebung sind anerkannt, es bedarf aber auch heute immer einer rechtfertigenden Indikation, auch zur Röntgendiagnostik. Der kindliche Organismus ist im Vergleich zum Erwachsenen strahlensensibler und damit anfälliger, durch ionisierende Strahlen Malignome zu entwickeln, auch weil die jungen Patienten eine längere Lebenserwartung und damit Zeitspanne haben [ 7 , 30 , 41 , 46 ].…”
Section: Diskussionunclassified
“…As a corollary, about 72% of European countries as well as the United States have established DRLs for some radiological examinations and subsequent reviews have demonstrated significant dose reductions (16%-30%) [8,13], such evidences are difficult to come by in Africa. Only about eight out of fiftyfour countries in Africa (15 %) have publications on DRLs, with no evidence linking any country to national DRLs [14]. Regulatory agencies have dual obligations with regards to the issue in focus.…”
Section: Diagnostic Reference Levels For Patientsmentioning
confidence: 99%
“…Non-availability of national or local DRLs also contributes to this lack of optimization as few countries have developed such tools. 35…”
Section: Limited or Absent Optimization Of Radiation Protection And Safetymentioning
confidence: 99%